Present issues and efforts to integrate sustainable development goals in a local senior high school in Japan: A case study - Kazuaki Okubo; Jeongsoo Yu; Shiori Osanai; Kevin Roy B. Serrona (Journal of Urban Management, 2021)
In this paper, we investigate the present situation and issues concerning efforts to integrate sustainable development goals (SDGs) education into the curriculum of a Japanese senior high school. We observed the implementation of SDGs-relevant courses for one year and conducted a questionnaire survey to grasp the teachers' attitudes toward SDGs education. Based on these data, we identify the difficulties related to SDGs education, such as discrepancies of interest in SDGs between teachers and students, teachers' lack of knowledge about SDGs, and so on. We also note the positive impacts of collaboration among local stakeholders during the course of raising teachers' understanding and attitudes toward SDGs education.
Keywords: 710; Education; Japan; Senior high schools; Sustainable development goals